2009
DOI: 10.1262/jrd.20169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postnatal Administration of Diethylstilbestrol on Puberty and Thyroid Function in Male Rats

Abstract: Abstract.To examine the effects of diethylstilbestrol (DES) on male pubertal development and thyroid function, juvenile male Sprague-Dawley rats were given DES daily by oral intubation at doses of 10, 20 and 40 μg/kg/day from postnatal day 33 for 20 days. Prepuce separation was significantly delayed at the dose of 20 μg/kg/day and above in the DES-treated rats. DES treatment induced a significant reduction in the weights of testes, epididymides, the ventral prostate, seminal vesicles plus coagulating glands an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Therefore, chronic corticosterone suppression induced by DES has the potential to disrupt the regulators of endocrine homeostasis and to facilitate the impairment of stress resistance. These findings constitute a new and important step towards understanding the mechanisms behind DES toxicity, such as reduced fertility, increased vaginal adenocarcinoma, and reduced testicular size and sperm count (Schrager & Potter 2004, Shin et al 2009, Unüvar & Büyükgebiz 2012. It is difficult to elucidate the mechanism of DES toxicity over the long term from the foetal stage to adulthood due to multiple hormone-related events such as foetal development, delivery and puberty.…”
Section: Figurementioning
confidence: 99%
“…Therefore, chronic corticosterone suppression induced by DES has the potential to disrupt the regulators of endocrine homeostasis and to facilitate the impairment of stress resistance. These findings constitute a new and important step towards understanding the mechanisms behind DES toxicity, such as reduced fertility, increased vaginal adenocarcinoma, and reduced testicular size and sperm count (Schrager & Potter 2004, Shin et al 2009, Unüvar & Büyükgebiz 2012. It is difficult to elucidate the mechanism of DES toxicity over the long term from the foetal stage to adulthood due to multiple hormone-related events such as foetal development, delivery and puberty.…”
Section: Figurementioning
confidence: 99%
“…Treatment of male rats with estrogens is known to decrease production of the gonadotropins follicle stimulating hormone (FSH) and luteinizing hormone (LH), which in turn reduces production of androgens by the testes, resulting in atrophy of the androgen dependent reproductive tissues (Shin et al 2009). In accord with this observation, micro-array data from our laboratory indicate the mRNAs encoding the beta subunits of both FSH and LH were dramatically reduced in response to DES treatment in both male ACI and male BN rats (manuscript in preparation; Tong et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Besides testosterone, decreased production of folliclestimulating hormone (FSH) and luteinizing hormone (LH) was also observed (Shin et al, 2009;Warita et al, 2006). Kobayashi et al (2009) conceded to the negative impact of steroidogenesis, but suggested that there was an increase in androgen receptor (AR) expression to compensate.…”
Section: Resultsmentioning
confidence: 99%